2013
DOI: 10.1016/j.pragma.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal analysis of facework strategies in a corpus of charity ads on British television

Abstract: The aim of this article is to carry out a qualitative multimodal analysis of the codification of verbal and nonverbal politeness strategies in a sub-corpus of five charity commercials aired on British television. Brown and Levinson's (1978, 1987) verbal politeness strategies are taken as a starting point together with a detailed analysis of facework that is realized through paralinguistic and extralinguistic modes of communication (Kress and van Leeuwen, 1996;Machin, 2010). In what we have identified as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This is what was observed in a qualitative study of five British charity commercials, which were found to use politeness strategies to soften their requests-for example, phrasing the request as a question such as 'We save the children; will you?' (Pennock-Speck & Saz-Rubio, 2013). It is however easy to find examples that do not fit that template.…”
mentioning
confidence: 99%
“…This is what was observed in a qualitative study of five British charity commercials, which were found to use politeness strategies to soften their requests-for example, phrasing the request as a question such as 'We save the children; will you?' (Pennock-Speck & Saz-Rubio, 2013). It is however easy to find examples that do not fit that template.…”
mentioning
confidence: 99%
“…A possible explanation is that there is a balance between deferring to the addressee and insisting on the merits of a particular product. Too much deference might suggest that the product is not as good as it should be (Pennock-Speck and del Saz-Rubio, 2013: 51). Furthermore, copywriters know that viewers do not expect or indeed want the same politeness conventions from an anonymous VO as they would from a conversational partner.…”
Section: Discussionmentioning
confidence: 99%
“…In linguistic studies of politeness, the British National Corpus 1 , both text and audio, is also often used (McEnery et al, 2002;Deutschmann, 2006;Vizcaíno, 2007). Additionally, there are a number of works on polite communication that use a range of multimedia corpora: political comics corpora (Abdel-Raheem, 2021), the Santa Barbara series corpora (Brown, 2014) and studies on TV charity commercials (Pennock-Speck and del Saz-Rubio, 2013). These studies show that corpora annotated with paraverbal features are important for a deeper study of politeness.…”
Section: Politeness and Multimedia Corporamentioning
confidence: 99%